(3JSWjM GdcQIs - (3CHh GdaJhM fLe GdOjf CMeO Hf eMeO Hf GdSQj GdHZOGOj, GHf GdUdGM,J (B548 (3g` s
(3ChdgG (B:s
(3jHOC Hbhdg LejY GdOhGFQ GdYXGe ai GdcQI HbSe GdeOGQGJ GdehGRfI deYOd GdfgGQ (B( (3ef GdebGdI GdChdi (B) s
(3BNQgG (B:s
(3hgcPG jOGQ Ydi SGFQ GdCbSGe HehVY GdbSeI hPdc eG CQOfG s
(3GdebGdI GdChdi ai GdbSe GdYdei hGdKGfjI ai GdbSe GdYdedi hgPG GdeNWhW YHGQI Yf GdbSe GdKGfi hUaMI ef GdbSe GdChds
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs